Pelatihan Pembukuan Sederhana bagi Penenun Ulos di Desa Sigaol - Simanjuntak, Sri Ida Royani; Simanjuntak, Juara; Tanjung, Ribka C (AJAD : Jurnal Pengabdian kepada Masyarakat, 2024)
Community service activities are by providing training on simple bookkeeping for ulos weavers in Sigaol Village, Uluan District, Toba Regency. This village has a livelihood as farmers for the fathers while the mothers carry out ulos weaving activities, with the aim of helping the household economy. The ulos they weave are ulos from the Toba and Simalungun areas. With various types of motifs that exist, including the hotang yeast motif, the maratur star motif, the mangiring motif, the tonga tonga motif for pucca, the simarhapisoran motif and so on. Many of the mothers who do ulos weaving business without having the knowledge and skills about the importance of simple bookkeeping, they only run by relying on the understanding of the estimate that there will be money coming in that can finance daily activities. The method in this PKM activity is socialization and practice. This PKM activity has positive implications and impacts for ulos weavers. The results of this service implementation activity illustrate that the MSME participants who attended the training totaling 20 people have understood the importance of simple bookkeeping and have been able to prepare simple financial reports